Targeting dormant phenotype acquired mycobacteria using natural products by exploring its important targets: In vitro and in silico studies - Sharma, Shweta; Chikhale, Rupesh; Shinde, Nivedita; Khan, A. M.; Gupta, Vivek Kumar (Frontiers in Cellular and Infection Microbiology, 2023)
The dormant phenotype of Mycobacterium tuberculosis which develops during infection poses a major challenge in disease treatment, since these bacilli show tolerance to front-line drugs. An in vitro hypoxia dormancy model was established which produced phenotypically dormant Mycobacterium smegmatis after prolonged incubation under conditions of low oxygen, low pH, and nutrient limitation. Bacilli in this model displayed the classical dormancy characters, including loss of acid fastness, altered morphology and most importantly, tolerance to front-line drugs. The dormant form of M. smegmatis was treated with drugs and phytomolecules. Three phytomolecules exhibited activity against dormant bacilli, as shown by lack of regrowth in solid and liquid media. Further investigation of dormancy-active hits was carried out using in silico approaches to understand the druggable targets of these phytomolecules in dormant bacilli. For this study, molecular docking, molecular dynamics simulations (MDS) and molecular mechanics-generalized born solvent accessibility (MM-GBSA) based binding energy (∆Gbind) calculations were performed. Five different targets, isocitrate lyase (ICL), GMP synthase, LuxR, DosR and serine/threonine protein kinase (STPK) from the M. smegmatis and M. tuberculosis were studied in details. DosR and STPK were found to be the common targets in both the species that were more prone to the phytomolecules. The standard DosR inhibitor, HC104A showed a lower dock score and binding energy -4.27 Kcal/mol and -34.50 Kcal/mol respectively compared to the natural products under study. Phytomolecule, icariin showed better docking score (dock Score = -5.92 Kcal/Mol with and binding energy ∆Gbind= -52.96 Kcal/mol) with DosR compared to known DosR inhibitor, HC104A (dock score = -4.27 Kcal/mol and binding energy ∆Gbind = -34.50 Kcal/mol). Similarly, the known STPK inhibitor MRCT67127 showed a lower dock score and binding energy -4.25 Kcal/mol and -29.43 Kcal/mol respectively compared to the phytomolecule icariin (dock Score = -5.74 Kcal/Mol and ∆Gbind= -43.41 Kcal/mol). These compounds might ultimately lead to new therapeutics or may be useful as adjuvants to the first line drugs to reduce the lengthy anti-TB therapy in future.